Couples' labour supply responses to job loss: Boom and recession compared - Mark Bryan; Simonetta Longhi (University of Essex, Institute for Social and Economic Research (ISER), 2013)
We examine how couples' labour supply behaviour in the UK responds to a job loss by one partner, using the Labour Force Survey to compare the period of growth of 1995-2007 to the Great Recession and its aftermath of 2008-11. In single earner couples during the recession, both men and women substantially increased their job search activity following a partner's job loss, while the increase in search during the boom was smaller (and non-existent for men). However, the increase in job search during recession did not appear to translate into more success in finding work for either men or women. Among dual earner couples, we find little evidence that individuals searched for alternative jobs or tried to increase their hours if their partner lost their job, except that women working part-time were more likely to start looking for another job. Both men and women were more likely to quit their job voluntarily if their partner lost their job, but the recession seems to have made people more cautious about voluntarily quitting their job. We find little evidence that people react in advance of job losses, suggesting that unemployment typically comes as a surprise.
Keywords: J22; J64; 330; Added-worker effect; recession; employment; household labour supply